Exploring the relationships between innovation and internationalization of small and medium‐sized enterprises: A nonrecursive structural equation model. (18th December 2013) - Halilem, Norrin; Amara, Nabil; Landry, Réjean
Abstract This article seeks to provide more insights on the two‐way link between internationalization and innovation by considering total, direct, and reciprocal effects using a nonrecursive structural model. Innovation is defined through product and process development, while internationalization is defined through inward and outward internationalization in both closer and farther markets. The results suggest that these two major sources of growth are linked by different sets of relations, from the investment in product and process innovation to outward internationalization in a closer market, or from inward and outward internationalization in farther markets to the investment in product innovation. Copyright © 2013 ASAC. Published by John Wiley & Sons, Ltd.